TiO2 as Photosensitizer and Photoinitiator for Synthesis of Photoactive TiO2-PEGDA Hydrogel Without Organic Photoinitiator - Glass, Sarah; Trinklein, Betsy; Abel, Bernd; Schulze, Agnes (Frontiers in Chemistry, 2018)
The replacement of potentially toxic photoinitiators is of increasing interest regarding the synthesis of biomaterials by photopolymerization. Therefore, we present a new method for the preparation of UV polymerized hydrogels with TiO2 as a photoinitiator. Titania is known to be an excellent photoactive compound which is nontoxic, inert, and cheap. The so-formed hydrogels possess excellent mechanical properties, a high swelling ratio, and high thermal stability. Furthermore, no TiO2 is released from the hydrogels. Thus, the material is highly suitable for medical applications. Additionally, the present TiO2 in the hydrogels remains photoactive as demonstrated by degradation of methylene blue. This enables the application of TiO2-hydrogels in photodynamic therapy.